1993
DOI: 10.1148/radiology.186.3.8430168
|View full text |Cite
|
Sign up to set email alerts
|

Lung parenchymal changes secondary to cigarette smoking: pathologic-CT correlations.

Abstract: To determine the histopathologic basis for computed tomographic (CT) interpretation of smokers' lung and the accuracy of CT in the detection of alterations related to cigarette smoking, parenchymal lung lesions were studied from 41 heavy smokers who underwent thoracotomy for removal of a solitary pulmonary nodule. CT scanning of the resected lungs, corresponding exactly to the sections seen on preoperative CT scans, resulted in the following pathologic-CT correlations. Areas of ground-glass attenuation seen on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 0 publications
7
68
0
1
Order By: Relevance
“…[1][2][3][4][5][6] When associated with clinical symptoms of shortness of breath and cough, pulmonary function abnormalities of mixed restrictive and obstructive lung disease and high resolution CT scanning demonstrating centrilobular micronodules, ground glass opacities and peribronchiolar thickening, a diagnosis of respiratory bronchiolitisassociated interstitial lung disease can be considered. [7][8][9][10][11][12][13][14] While the above small airway changes and airspace macrophages have been areas of primary pathologic interest, Fraig et al and others have also pointed out that very mild degrees of centrilobular alveolar septal and focal subpleural fibrosis can be present in nearly 50% of respiratory bronchiolitis cases. 6,9,15,16 This collagenous thickening of the alveolar septa can be dramatic and is the basis for this report of nine cases referred for consultation with the diagnosis of fibrotic phase of nonspecific interstitial pneumonia, but instead are interpreted as a form of respiratory bronchiolitis-associated interstitial lung disease with pronounced panlobular and subpleural alveolar septal fibrosis occurring in the presence of emphysematous change.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] When associated with clinical symptoms of shortness of breath and cough, pulmonary function abnormalities of mixed restrictive and obstructive lung disease and high resolution CT scanning demonstrating centrilobular micronodules, ground glass opacities and peribronchiolar thickening, a diagnosis of respiratory bronchiolitisassociated interstitial lung disease can be considered. [7][8][9][10][11][12][13][14] While the above small airway changes and airspace macrophages have been areas of primary pathologic interest, Fraig et al and others have also pointed out that very mild degrees of centrilobular alveolar septal and focal subpleural fibrosis can be present in nearly 50% of respiratory bronchiolitis cases. 6,9,15,16 This collagenous thickening of the alveolar septa can be dramatic and is the basis for this report of nine cases referred for consultation with the diagnosis of fibrotic phase of nonspecific interstitial pneumonia, but instead are interpreted as a form of respiratory bronchiolitis-associated interstitial lung disease with pronounced panlobular and subpleural alveolar septal fibrosis occurring in the presence of emphysematous change.…”
mentioning
confidence: 99%
“…In other words, ground-glass attenuation could reflect "smoker's alveolitis" whereas micronodules would correspond to respiratory bronchiolitis [15,16] (as can be observed in the morphologic appearance from a surgical biopsy performed on patient 3 -figure 3). Lung function tests, shown in table 3, were performed on seven patients.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that respiratory illness is associated with the degree of tobacco smoke exposure in particular [5,11]. The pathological entity of smokeinduced RB-ILD is also called ''smokers' bronchiolitis'' as it is seen almost exclusively in current or former smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The common finding of ''dirty chest'', an overall increase in non-specific lung markings on chest radiography in such patients, is frequently identified in daily routine [7][8][9][10]. Remy-Jardin et al [11] found that the morphological substrate of cigarette smoking-induced changes in chest radiography were parenchymal micronodules and intralobular opacities comparable to the findings in anthracosilicosis of coal workers. Therefore, we hypothesised that it might be possible to quantify the smoking-induced changes of the lung using the International Labour Organization (ILO) classification [12].…”
mentioning
confidence: 97%